An inexact conjugate gradient method for symmetric nonlinear equations. Issue 6 (23rd October 2019) - Abubakar, Auwal Bala; Kumam, Poom; Awwal, Aliyu Muhammed
Abstract : In this article, we present a conjugate gradient method for large‐scale nonlinear equations with symmetric Jacobian. The method is a modification of the descent Dai‐Liao conjugate gradient method for unconstrained optimization problem proposed by Kafaki and Gambari. Under some assumptions, which include symmetric property of the Jacobian, we establish the global convergence of the proposed method and, finally, some numerical results to show its efficiency.